Application of Different Fertilizers Type and Concentration on Growth and Yield of Pakcoy (Brassica Rapa L.) in Hydroponic System - Andhini Siti Fatiha; Anthony Walsen; Herman Rehatta (Agrologia, 2022)
Nutrition is an important factor for pakcoy cultivation in a hydroponic system so that the growth media should contain appropriate concentration of micro- and macronutrient to support plant growth. This study has been done to determine the different effect of the different liquid organic fertilizer type and concentration compared to AB Mix fertilizer on the growth and yield of pakcoy grown with the Hydroponic System. The experiment was conducted by using completely randomized design consisting of 9 combination treatments of type and concentration of liquid fertilizer.  The treatments were AB Mix Fertilizer with a concentration of 10 ml/l, 12 ml/l, 14 ml/l; Meroke Liquid Fertilizer with a concentration of 16 ml/l, 18 ml/l, 20 ml/l; and Nasa Liquid Organic Fertilizer with a concentration of 5 ml/l, 10 ml/l, 15 ml/l. The results showed that the application of 20 ml/l of Meroke liquid fertilizer significantly increased plant height, number of leaves, leaf area, plant fresh weight, and plant dry weight compared to another treatments. However it did not affect root length.